Relationship between emotional expressions and lifestyle changes among university students during COVID-19 lockdown in Lebanon - José-Noel Ibrahim; Chirine Fares; Robert Bader (Journal of Infection in Developing Countries)
Introduction: Emotional expressivity plays an important role in terms of communication and interpersonal relationships in the context of society. Our research aims at assessing the perception of emotional expressivity and its association with lifestyle changes during COVID-19 lockdown among university students in Lebanon.